Applications Of Artificial Intelligence In Environmental Pollution - Lim, Jing Hui (2022)
Real-life environmental issues are complex and highly dependent on various operating conditions, feedwater characteristics and process configurations. As the problems of environmental pollution become more complex, researchers are exploring and studying computationally rigorous intelligent systems for intelligent solutions. Therefore, this study aims to investigate the applications, issues, and challenges of AI-based models in the field of environmental pollution. The objectives of this study are to review the concepts of AI and environmental pollution, conduct the Strength, Weakness, Opportunity, and Threat (SWOT) Analysis of the deployment of AI in environmental pollution, and propose the future trends of AI implementation in the environmental pollution.In this study, a qualitative approach was used in which a total of 191 research articles were extensively reviewed. The SWOT analysis was conducted to assess the potential issues and challenges AI encountered in environmental pollution. The analysis revealed that current AI applications in environmental pollution can produce reliable, accurate and precise outcomes but lack transparency due to unexplainable behaviour. The PESTLE analysis has also been included in this research, which discussed AI application of environmental pollution in political, economic, sociological, technological, legal and environmental factors. At the conclusion of this study, a probable future development of AI in environmental pollution is offered. It is expected that more decision-making systems can be proposed and developed to perform complex environmental decision-making.Last but not least, this research helps to a better understanding of how AI technology was accepted and exploited in environmental pollution. This study can also be used as a reference source for other researchers performing similar research.